2014
DOI: 10.1103/physreva.89.053617
|View full text |Cite
|
Sign up to set email alerts
|

Radio-frequency spectroscopy of polarons in ultracold Bose gases

Abstract: Recent experimental advances enabled the realization of mobile impurities immersed in a Bose-Einstein condensate (BEC) of ultracold atoms. Here, we consider impurities with two or more internal hyperfine states, and study their radio-frequency (rf) absorption spectra, which correspond to transitions between two different hyperfine states. We calculate rf spectra for the case when one of the hyperfine states involved interacts with the BEC, while the other state is noninteracting, by performing a nonperturbativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
188
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(193 citation statements)
references
References 94 publications
(195 reference statements)
4
188
1
Order By: Relevance
“…(23) and allowing p to be finite. The effective polaron mass can then be analyzed as previously demonstrated [59].…”
Section: Discussionmentioning
confidence: 99%
“…(23) and allowing p to be finite. The effective polaron mass can then be analyzed as previously demonstrated [59].…”
Section: Discussionmentioning
confidence: 99%
“…Lots of theoretical efforts have been paid to study the Fermi polaron [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and the Bose polaron [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Nearby a Feshbach resonance, a Fermi polaron displays an attractive branch [20][21][22][23][24][25]29] and a repulsive branch [26][27][28], which directly manifests two-body correlations in this system.…”
mentioning
confidence: 99%
“…In Refs. [44,45] it has been shown that the dynamics of such a system can be described by the Fröhlich Hamiltonian. In an inhomogeneous gas, i.e., a gas with a spatially dependent density profile, this Hamiltonian differs from the QBM one due to the nonlinear dependence of the interaction term on the position of the impurity.…”
Section: A Hamiltonian and Lindblad Mementioning
confidence: 99%
“…An immediate application of this generalization concerns the physical behavior of an impurity embedded in an ultracold gas. In this case spatial inhomogeneities are due to the presence of trapping potentials and, possibly, stray fields [44,45]. Here, we will study in detail the case when the coupling depends quadratically on the position of the test particle, and we will refer to this case with the name "quadratic QBM".…”
Section: Introductionmentioning
confidence: 99%